A prioritization approach upon non-functional and functional user stories in agile-scrum software development i-USPA: a preliminary results - Borhan, Noor Hazlini; Zulzalil, Hazura; Hassan, Sa’adah; Mohd Ali, Norhayati (IJMSAT, 2021)
Some studies claimed that negligence of non-functional user stories become the cause to failure of software products. Indeed, to achieve a high-quality software product, during the prioritization process, both functional and non-functional user stories should take into account. Although several prioritizations for user stories have been proposed so far, however, it does not provide a specific approach or technique to consider both functional and non-functional user stories during the prioritization process. Non-functional user stories are being neglected because functional user stories are considered to be more important than non-functional user stories, lack of knowledge and methodologies to accomplish non-functional user stories and the nature of Agile Software Development process itself. Therefore, this study aims to enhance the process of user stories prioritization by integrating the functional and non-functional user-stories concurrently in Agile-Scrum Software Development. This integrated technique is called as Integrated User Story Prioritization Approach (i-USPA). The studies showed the highly need of improving the user stories prioritization process would assist the Product Owner and the stakeholders to effectively prioritize the user stories process of software products. The implemented i-USPA has been evaluated through evaluation survey which addressed directly to Scrum practitioners. Its suitability and effectiveness in prioritizing user stories in Sprint Backlog will be measured based on evaluation survey feedbacks. Hence, this study concludes that i-USPA is suitable to be used for prioritizing user stories in Scrum project. It was believed the enhanced process can reduce the required time to perform the user stories prioritization task.